1997
DOI: 10.1007/s002239900230
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 2 (BMP-2) Enhances BMP-3, BMP-4, and Bone Cell Differentiation Marker Gene Expression During the Induction of Mineralized Bone Matrix Formation in Culturesof Fetal Rat Calvarial Osteoblasts

Abstract: Normal bone formation is a prolonged process that is carefully regulated and involves sequential expression of growth regulatory factors by osteoblasts as they proliferate and ultimately differentiate. Since this orderly sequence of gene expression by osteoblasts suggests a cascade effect, and BMP-2 is capable of initiating and maintaining this effect, we examined the effects of BMP-2 on expression of other BMPs and compared these effects with the expression pattern of bone cell differentiation marker genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(159 citation statements)
references
References 30 publications
8
142
1
5
Order By: Relevance
“…Since several studies have reported the possible involvement of CK2 and its effect Akt in bone metabolism (Bragdon et al, 2010;Moon et al, 2012), here we evaluated and found the antiosteoclastogenic and anabolic activity of CX-4945; CX-4945 inhibited the RANKL-induced osteoclast differentiation accompanied with suppression of Akt/NFATc1 signaling axis, but it enhanced the BMP-2-induced osteoblast differentiation via the ERK1/2-Smad signaling axis. Since BMP-2 enhances the expression of other BMP genes during osteoblast differentiation (Chen et al, 1997;Kawai et al, 2006), these reports demonstrate that CX-4945 could enhance the BMP-2-induced increases in ALP and BMP-4 mRNA levels (Fig. 3C).…”
Section: Discussionmentioning
confidence: 72%
“…Since several studies have reported the possible involvement of CK2 and its effect Akt in bone metabolism (Bragdon et al, 2010;Moon et al, 2012), here we evaluated and found the antiosteoclastogenic and anabolic activity of CX-4945; CX-4945 inhibited the RANKL-induced osteoclast differentiation accompanied with suppression of Akt/NFATc1 signaling axis, but it enhanced the BMP-2-induced osteoblast differentiation via the ERK1/2-Smad signaling axis. Since BMP-2 enhances the expression of other BMP genes during osteoblast differentiation (Chen et al, 1997;Kawai et al, 2006), these reports demonstrate that CX-4945 could enhance the BMP-2-induced increases in ALP and BMP-4 mRNA levels (Fig. 3C).…”
Section: Discussionmentioning
confidence: 72%
“…Mid-and late-stage osteogenic markers including OPN, bone sialoprotein (BSP), and OCN are temporal successors to RUNX2 and OSX expression after rhBMP-2 stimulation [63]. The complex temporal expression profiles of OPN, BSP, and OCN have been elucidated [15,16,23,25,26,30,53,59,66]; therefore, a coordinated, temporal RNAi treatment cycle may enhance the duration and intensity of gene silencing and prevent HA deposition in vitro. Consequently, the evolution of RNAi therapeutics must match RNAi targets to their expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…LTBP1 Stably Expressing Cell Lines-To generate UMR-106 cell lines stably overexpressing LTBP1, a full-length human LTBP1 construct in the PSV7d vector (kindly provided by K. Miyazono, Japanese Foundation for Cancer Research, Tokyo) was co-transfected at a 10:1 ratio with an RSVneo selection vector, using calcium phosphate precipitation as described elsewhere (33). The transfected cells were selected with 400 g/ml G418, and resistant single cell clones were screened for LTBP1 expression using an ELISA, as described previously (7).…”
Section: Methodsmentioning
confidence: 99%